Genome Sequence Analyses of Pseudomonas savastanoi pv. glycinea and Subtractive Hybridization-Based Comparative Genomics with Nine Pseudomonads - Qi, Mingsheng; Wang, Dongping; Bradley, Carl A.; Zhao, Youfu (PLOS ONE, 2011)
Bacterial blight, caused by Pseudomonas savastanoi pv. glycinea (Psg), is a common disease of soybean. In an effort to compare a current field isolate with one isolated in the early 1960s, the genomes of two Psg strains, race 4 and B076, were sequenced using 454 pyrosequencing. The genomes of both Psg strains share more than 4,900 highly conserved genes, indicating very low genetic diversity between Psg genomes. Though conserved, genome rearrangements and recombination events occur commonly within the two Psg genomes. When compared to each other, 437 and 163 specific genes were identified in B076 and race 4, respectively. Most specific genes are plasmid-borne, indicating that acquisition and maintenance of plasmids may represent a major mechanism to change the genetic composition of the genome and even acquire new virulence factors. Type three secretion gene clusters of Psg strains are near identical with that of P. savastanoi pv. phaseolicola (Pph) strain 1448A and they shared 20 common effector genes. Furthermore, the coronatine biosynthetic cluster is present on a large plasmid in strain B076, but not in race 4. In silico subtractive hybridization-based comparative genomic analyses with nine sequenced phytopathogenic pseudomonads identified dozens of specific islands (SIs), and revealed that the genomes of Psg strains are more similar to those belonging to the same genomospecies such as Pph 1448A than to other phytopathogenic pseudomonads. The number of highly conserved genes (core genome) among them decreased dramatically when more genomes were included in the subtraction, suggesting the diversification of pseudomonads, and further indicating the genome heterogeneity among pseudomonads. However, the number of specific genes did not change significantly, suggesting these genes are indeed specific in Psg genomes. These results reinforce the idea of a species complex of P. syringae and support the reclassification of P. syringae into different species.